Pemikiran Pendidikan Islam Al-Zarnuji dan Relevansinya dengan Pendidikan Islam Kontemporer - Awaluddin, Raisa Zuhra Salsabila (TAUJIH: Jurnal Pendidikan Islam, 2023)
The purpose of this paper is to get explanation of Al-Zarnuji's thought in his book and its relevance to contemporary Islam. contemporary Islam. The field of education is currently facing numerous challenges in light of the era of easy access to information. Education is not only about imparting knowledge, but also about fostering good character, improving morals, and adding value to students. In order to address these challenges, it is imperative to instill good morals in individuals, which will enable them to refrain from engaging in bad and uneducated actions. Al-Zarnuji, in his book, emphasizes the need for moral education, which he compiled by seeking knowledge. This study employs qualitative research, specifically library research, and utilizes Ta'lim Al-Muta'allim as the primary data source, along with articles, books, and theses as secondary data sources. The analysis technique employed is descriptive analytics. The results of this study reveal that Al-Zarnuji discusses how to seek knowledge and advice in his book Ta'lim Al-Muta'allim, which comprises 13 chapters discussing knowledge, educators, and students, among other topics. The relevance of this book to contemporary education lies in its emphasis on seeking knowledge for the affairs of the hereafter, with worldly affairs being secondary. The curriculum of religious science and general science is also discussed, with individuals being able to choose one science and utilize discussion methods. In modern society, characterized by the digital age, morals are essential in order to prevent individuals from engaging in bad actions and to obtain good information.